Pengaruh Iklan Instagram, Content Marketing, Interaktivitas Media Sosial Terhadap Minat Menggunakan Jasa BLOOMS Wedding Organizer - Dimas Maulana Afwaroh; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The rapid growth of the wedding organizer industry in Indonesia has intensified competition, encouraging firms to adopt effective digital marketing strategies. Instagram has become a dominant platform due to its visual advertising features, content marketing capabilities, and interactive communication with potential consumers. This study aims to analyze the influence of Instagram advertising, content marketing, and social media interactivity on consumers’ intention to use BLOOMS Wedding Organizer services in Malang City. The research is grounded in the Theory of Reasoned Action, which explains that behavioral intention is formed through attitudes and subjective norms shaped by marketing stimuli.This study employed a quantitative associative research design. Data were collected using an online questionnaire with a Likert scale distributed to 104 Instagram users aged 20–35 years who were familiar with BLOOMS Wedding Organizer. Purposive sampling was applied to ensure respondent relevance. Data analysis was conducted using multiple linear regression with SPSS, supported by validity tests, reliability tests, classical assumption tests, and hypothesis testing. The results indicate that Instagram advertising, content marketing, and social media interactivity have positive and significant effects on consumers’ intention to use BLOOMS Wedding Organizer services. This finding confirms the importance of integrated digital marketing strategies in wedding services industry. Keywords: Instagram Advertising, Content Marketing, Social Media Interactivity, Purchase Intention, Wedding Organizer